Analisis Pernyataan “Utamakan Bahasa Indonesia”: “Ada Apa dan Mengapa?” - Ary Setyadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
The statement "PRIORITY ENGLISH" is interestingly discussed, because it evokes a speaker's reaction; so that there is an "interpretation": What is it? "what is the command: appeal, petition, solicitation, warning, concern, concern and command of suspicion. The existing statement as the CAPS, while the "interpretation" as the CONSEQUENCES. From the question "What's wrong?" The question "Why?" As the "(basic) cause" of the seventh "interpretation" came into question. The answer to the question "Why" includes: dynamic, prestige, mixed code, (result) vocabulary wealth, (for) simplicity of form, (more) communicative, and (easy) vocabulary. The research method is based on three strategic stages, namely: 1. the data collection stage, that is by utilizing the interview and study (to) the library (an); 2. phase classification and data analysis, namely classification efforts based on the reference content of the meaning of data groups; while data analysis bases the application of linguistic theory, semantic fields and (theory) pragmatics. The application of linguistic theory, the semantic field, for the classification of data on the findings of "interpretation". The analytical method is based on "direct element division (IC), by technique: substitution, expansion, and paraphrase. While the application of (theory) pragmatic basing on `principle of cooperation`, namely` maxim implementation`; and `courtesy principle`, ie` match maxim`. The application of both theories is complementary.